uPA binding increases UPAR localization to lipid rafts and modifies the receptor microdomain composition - Sahores, Maria Macarena (2008)
UPAR is a GPI anchored protein, which is found in both lipid rafts and in more fluid regions of the plasma membrane. We have studied the role of the ligand uPA on uPAR localization and on the composition of the lipid membrane microdomains. We have analyzed the glycosphingolipid environment of uPAR in detergent resistant membrane (DRM) fractions prepared by cell lysis with 1% Triton X-100 and fractionated by sucrose gradient centrifugation obtained from HEK293-uPAR cells. The uPAR specific lipid membrane microdomain has been separated from the total DRM fraction by immunoprecipitation with an anti-uPAR specific antibody under conditions that preserve membrane integrity. We have also tested uPA-induced ERK phosphorylation in the presence of methyl-β-cyclodextrin, which is known to disrupt lipid rafts by sequestering cholesterol from such domains. Our results show that uPAR is partially associated with DRM and this association is increased by ligands, is independent of the catalytic activity of uPA, and is required for intracellular signalling. In the absence of ligands, uPAR experiences a lipid environment very similar to that of total DRM, enriched in sphingomyelin and glycosphingolipids. However, after treatment of cells with uPA or ATF the lipid environment is strongly impoverished of neutral glycosphingolipids. © 2007.